Geographical indications (GI) registration in India: Present status and future prospects - R, Abdul Fiyaz; Ramya, K T; Ajay, B C; Azam, M M; Waris, Amtul (Indian Farming, 2020)
Geographical indications are the legal protection for goods which have enormous significance. India is bestowed with rich heritage of culture and traditions, that are flourishing here for past several centuries. In addition to this it has enormous biodiversity and has diverse agroclimatic conditions, which lead to many geographic specific IPR products in agriculture and other sectors. The GI registration has high significance in the country like India as it has been proven in the case of Basmati rice, where foreign exports earning is about ` 38,443 crore. Presently a limited number of commodities have been registered under GI and many more products belonging to different states have potential to be registered. The awareness about potential products with regard to process of registration and its social and economic benefit and significance among producers and traders have to be increased to get GI tag.